Plant speciation in continental island floras as exemplified by Nigella in the Aegean Archipelago - Comes, Hans Peter (The Royal Society, 2008)
Continental shelf island systems, created by rising sea levels, provide a premier setting for studying the effects of geographical isolation on non-adaptive radiation and allopatric speciation brought about by genetic drift. The Aegean Archipelago forms a highly fragmented complex of mostly continental shelf islands that have become disconnected from each other and the mainland in relatively recent geological times (ca <5.2 Ma). These ecologically fairly homogenous islands thus provide a suitable biogeographic context for assessing the relative influences of past range fragmentation, colonization, gene flow and drift on taxon diversification. Indeed, recent molecular biogeographic studies on the Aegean Nigella arvensis complex, combining phylogenetic, phylogeographic and population level approaches, exemplify the importance of allopatry and genetic drift coupled with restricted gene flow in driving plant speciation in this continental archipelago at different temporal and spatial scales. While the recent (Late Pleistocene) radiation of Aegean Nigella, as well as possible instances of incipient speciation (in the Cyclades), is shown to be strongly conditioned by (palaeo)geographic factors (including changes in sea level), shifts in breeding system (selfing) and associated isolating mechanisms have also contributed to this radiation. By contrast, founder event speciation has probably played only a minor role, perhaps reflecting a migratory situation typical for continental archipelagos characterized by niche pre-emption because of a long established resident flora. Overall, surveys of neutral molecular markers in Aegean Nigella have so far revealed population genetic processes that conform remarkably well to predictions raised by genetic drift theory. The challenge is now to gain more direct insights into the relative importance of the role of genetic drift, as opposed to natural selection, in the phenotypic and reproductive divergence among these Aegean plant species.